Analisis Classification Society Accessibility Holy Sumpur Districts to District General Hospital Sijunjung - Susanti, Mira; Ahmad, Ridwan; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
This study aims to determine the classification and level of public accessibility to the Holy Sumpur district general hospital district Sijunjung which includes: 1) distance to the Holy Sumpur district general hospital district Sijunjung, 2) public transport waiting time, 3) the condition of transportation infrastructure, 4) the condition of transportation facilities. Results of this study concluded, the classification of public accessibility to the Holy Sumpur district hospital district such Sijunjung using Black analysis: 1) from 3 villages (villages Holy Sumpur South, Mangganti villages, and Unggan) in the Holy Sumpur district, 2 villages (villages Mangganti , and villages Unggan) included into the low accessibility. 2) Holy Sumpur South medium including accessibility. 3) Most of the low level of accessibility in the district nagari Holy Sumpur in reaching the public hospital district Sijunjung caused by the distance 99 Km. 4) In addition to the distance factor prasaranan road conditions also account for the low access to public hospital districts such Sijunjung there are gravel roads and dirt road that connects the villages to the district general hospital Sijunjung. That there are gravel roads and dirt roads and villages are villages Mangganti Unggan. Public opinion about in reaching the public hospital district Sijunjung: 1) People assume that the distance from district to district general hospitals of district Sijunjung far is 96%. 2) People in Holy Sumpur district felt the waiting time for public transport to the district general hospital Sijunjung long that is equal to 85.3%. 3) Infrastructure of transport to reach the Holy Sumpur district general hospital district Sijunjung bad that is equal to 78.6%. 4) Means of transportation to reach the Holy Sumpur district general hospital district Sijunjung nothing is equal to 100%.